2017
DOI: 10.1038/ncomms15871
|View full text |Cite|
|
Sign up to set email alerts
|

ITK signalling via the Ras/IRF4 pathway regulates the development and function of Tr1 cells

Abstract: Type 1 regulatory T (Tr1) cells differentiate in response to signals engaging the T cell receptor (TCR), express high levels of the immunosuppressive cytokine IL-10, but not Foxp3, and can suppress inflammation and promote immune tolerance. Here we show that ITK, an important modulator of TCR signalling, is required for the TCR-induced development of Tr1 cells in various organs, and in the mucosal system during parasitic and viral infections. ITK kinase activity is required for mouse and human Tr1 cell differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 63 publications
2
74
0
Order By: Relevance
“…LAG3 and CD49b co-expression was previously reported to be a cell surface signature for both mouse and human IL-10-producing CD4 + T cells that lack the expression of Foxp3 (also known as type 1 regulatory T cells, Tr1 cells) [15]. We and others have previously reported that co-culturing murine naïve CD4 + T cells with antigen presenting cells (APCs) in the presence of anti-CD3, anti-CD28, anti-IFN-γ, anti-IL-12, and IL-27 can efficiently induce the differentiation of Tr1 cells [40; 43; 44], which express high levels of LAG3 and CD49b. Our recent data also demonstrated that this protocol can induce IL-10 production in bulk T cell populations that include both CD4 + and CD8 + T cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…LAG3 and CD49b co-expression was previously reported to be a cell surface signature for both mouse and human IL-10-producing CD4 + T cells that lack the expression of Foxp3 (also known as type 1 regulatory T cells, Tr1 cells) [15]. We and others have previously reported that co-culturing murine naïve CD4 + T cells with antigen presenting cells (APCs) in the presence of anti-CD3, anti-CD28, anti-IFN-γ, anti-IL-12, and IL-27 can efficiently induce the differentiation of Tr1 cells [40; 43; 44], which express high levels of LAG3 and CD49b. Our recent data also demonstrated that this protocol can induce IL-10 production in bulk T cell populations that include both CD4 + and CD8 + T cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IL-10 production can be significantly elevated in the pulmonary mucosa during the late stages of parasitic infection by Nippostrongylus brasiliensis ( Nb ), predominantly by CD4 + T cells that are LAG3/CD49b double positive [15; 45]. We recently observed that both Foxp3 − and Foxp3 + T cells are capable of producing IL-10 in the pulmonary tissues post Nb infection [40]. To determine whether co-expression of LAG3 and CD49b is exclusive to Foxp3 − Tr1 cell subset, we infected IL-10 GFP /Foxp3 RFP dual reporter mice with Nb , and analyzed the IL-10-producing T cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Triggering the TCR using anti-CD3 antibodies, has been shown to stimulate T cell activation and development in vivo (34), and we recently demonstrated that anti-CD3 antibody activates TCR and signals through ITK to drive type 1 regulatory T cell development in multiple organs (35). Given the observation that the lack of ITK, a TCR downstream mediator, is a negative tuner of CD8 + T cell HP, we examined the effect of TCR activation in regulating IL-7 mediated CD8 + T cell metabolism ( Figure 5C and Figure S3G&F).…”
Section: Tcr/itk Signals To Tune T Cell Hp and Metabolic Activitymentioning
confidence: 97%